Agrionympha, the long-known South African jaw moths: a revision with descriptions of new species (Lepidoptera, Micropterigidae) - Gibbs, George W.; Kristensen, Niels P. (Zootaxa, 2011)
The South African micropterigid genus Agrionympha Meyrick, 1921 has long been known from a single male specimen and very few females with three named species. This revision, based on more recent discoveries, brings the total named species to nine, by the addition of A. fuscoapicella sp. nov., A. jansella sp. nov., A. karoo sp. nov., A. kroonella sp. nov., A. pseudovari sp. nov., A. sagittella sp. nov., and notes the presence of a tenth species, represented only by two males in alcohol. The South Afrrican micropterigid fauna is thus quite diverse although, apart from the presence of another as yet undescribed genus, turns out to be a phenetically tightly-knit assemblage of highly conservative species. This revision provides a morphological description of males and females and includes larval features and a key to species. The micropterigid fauna of South Africa together with recently discovered taxa from Madagascar comprise part of what is regarded as the ‘southern sabatincoid’ lineage within the family—a weakly supported clade also including representatives from Australia, Chile, Ecuador, and Costa Rica. The survival of these small archaic rainforest moths in the face of increasing aridity is discussed.